GE_GERICHTE P/7211/2012 vom 17. Oktober 2016 - GE Cour de justice (2016)
IN DUBIO PRO REO ACTE D'ORDRE SEXUEL AVEC UNE PERSONNE DÉPENDANTE ; HONORAIRES ; DÉFENSE D'OFFICE | CEDH 6.3; CP 192.1; CPP 135.1